The abnormal implicit memory to positive and negative stimuli in patients with current and remitted major depressive disorder: A systematic review and meta-analysis - Liu, Xingze; Wang, Xiang; Liu, Yao; Gao, Feng; Xia, Jie; Fan, Jie; Zhu, Xiongzhao (Frontiers in Psychiatry, 2023)
In patients with current major depressive disorder (cMDD) a general abnormal implicit memory has been reported. However, the elaborate function of implicit memory when processing stimuli with different emotions (i.e., positive, neutral, and negative) in current and remitted (rMDD) patients is unclear. The present review examines implicit memory’s general and elaborate in cMDD and rMDD patients. We conducted meta-analyses based on published studies meeting criteria till July 2022 in Web of Science, PubMed, and EMBASE databases. Initial analyses of full sample patients (cMDD=601, rMDD=143) revealed a general implicit deficit in cMDD patients. Subsequent subgroup analyses showed that the implicit memory performance to neutral stimuli is poorer in cMDD patients than controls, but recovered in rMDD patients; the deficient implicit memory to positive stimuli existed in cMDD and rMDD patients; the implicit memory performance to negative stimuli in cMDD patients is similar to controls but poorer in rMDD patients. These findings indicate that the negative bias in cMDD patients might compensate for the general implicit memory deficit. Together, the implicit memory to neutral stimuli could recover with remission, whereas still abnormal in processing positive and negative stimuli. These results suggested that the abnormal implicit memory to positive and negative information might be relevant to depression pathogenesis.